Political violence against women in Brazil: expressions and definitions / Violência política contra as mulheres no Brasil: manifestações e definições - Biroli, Flávia (Revista Direito e Práxis, 2016)
DOI: 10.12957/dep.2016.25164 Abstract The article analyzes expressions of violence against women in Brazilian politics today. It discusses events that could be classified as political violence against women, setting an exploratory analysis. It also presents and discusses theoretical approaches, international laws and documents that have recently produced definitions and answers to this kind of violence. The present context of political violence against women in Brazil is addressed considering two different sets of events. The first consists in reactions to women’s rights in Congress, expressed in propositions and statements by Congress men. The second corresponds to representations of President Dilma Rousseff during the political process that resulted in her suspension in May 2016. Following those, it discusses theoretical approaches on violence against women as a group, as well as approaches that address political violence against women in recent studies, international laws and documents. A brief conclusion intends to contribute to a definition of political violence that involves practices targeting specific women and actions against women’s rights. Key-words: political violence against women; women’s rights; gender stereotypes; backlash; Brazil. Resumo O artigo analisa formas de violência política contra as mulheres no Brasil hoje, com a preocupação de discutir ao mesmo tempo manifestações empíricas que possam ser assim classificadas, abordagens teóricas dessa violência e leis e documentos internacionais que a tematizam. Situa o contexto político atual dessas manifestações e analisa dois conjuntos distintos de dados. O primeiro corresponde a reações contrárias aos direitos das mulheres no Congresso Nacional, expressas na forma de proposições e de enunciados de parlamentares em plenário. O segundo, por sua vez, corresponde a representações da presidenta Dilma Rousseff durante o processo político que resultou no seu afastamento em maio de 2016. Em seguida, discute abordagens teóricas sobre a violência contra as mulheres como grupo, assim como abordagens que tratam especificamente da violência política contra as mulheres em estudos recentes, leis e documentos internacionais. Uma breve conclusão pretende colaborar para uma definição de violência política que envolve práticas dirigidas a mulheres específicas e ações contra os direitos das mulheres. Palavras-chave: violência política contra as mulheres; direitos das mulheres; estereótipos de gênero, retrocessos; Brasil.